Leadership and Mediation Approaches for Social Cohesion in the Greek Public Sector - Kyriaki Aravidou; Sotiria Triantari; Ioannis Zervas (Administrative Sciences, 2025)
This study investigates how inclusive leadership, mentorship, and digital tools shape conflict prevention and social cohesion within the Greek public sector. Employing a cross-sectional quantitative design, data were collected from 203 employees across municipalities, ministries, regional, and decentralized administrations. The survey instrument captured four dimensions: leadership and mediation for social cohesion, mentorship for the empowerment of vulnerable groups, use of digital tools, and the perceived social impact of inadequate conflict management. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test direct and indirect effects, evaluate the explanatory and predictive power of the model, and explore the mediation mechanisms linking leadership, mentorship, and digital tools to social cohesion. The results demonstrate that both leadership and mentorship are positively perceived and significantly interrelated, jointly enhancing workplace cohesion and trust. Mentorship emerged as a critical predictor of digital tool adoption, highlighting its role as a bridge for digital inclusion and organizational innovation. In contrast, digital tools, despite their high importance in the model, remain underutilized and require further investment in training and integration. Poor conflict management is perceived as a major organizational risk, strongly linked to increased stress, diminished trust, and a deteriorated workplace climate. These findings highlight the value of integrating mentorship and inclusive leadership with mediation and digital technologies, supporting the development of hybrid strategies for conflict management. The study enriches theoretical debates on organizational resilience and social cohesion, while offering practical recommendations for modernizing public administration through participatory leadership, targeted mentoring programs, and the thoughtful adoption of digital solutions.